Digital entrepreneurship : theory & cases - Herlache, Michael, ....- (Createspace Independent Publishing Platform : Scotts Valley, 2015)
All new ventures start as social networks around a value theme. From this social network, additional functionality in the form of custom mods emerge along with corresponding business models. All digital ventures should thus begin as php social networking platforms acquiring users and then after seed funding begin the work on custom mods and monetizing via business models. The practice of entrepreneurship involves utilizing a diversification strategy to bring down entrepreneurial risk coupled with a white label strategy to cut down on startup costs and time to prototype. From there we have the purchase of an opt-in database including emails and the consequent upload to the white label platform. We then have user conversions generated from email campaigns via SMTP. Next, when there is significant enough traction in the form of user conversions we have funding rounds beginning with pre-seed, followed by seed, Series A, Series B, Series C, Series D+. Finally, we have the cash out by the entrepreneur in the form of an exit. The entrepreneur is then free to diversify their cash and reinvest it into his various startups to then repeat the process.
Keywords: Digitaal ondernemen; Ondernemen ; innovatie